Overview of the current status of Charipinae (Hymenoptera, Cynipoidea, Figitidae): taxonomy, distribution, and diversity - Ferrer-Suay, Mar; Pujade-Villar, Juli; Selfa, Jesús (Zootaxa, 2023)
The subfamily Charipinae (Hymenoptera: Cynipoidea: Figitidae) has had a problematic taxonomic history as many species have been described without comprehensive revisions being undertaken. Reliably identifying these species based on morphological assessment has been almost impossible. Recently, the types of all species have been re-examined and photographed, resulting in numerous taxonomic corrections that have been published elsewhere. Consequently, a summary checklist of all species that have ever been described within the Charipinae is provided with their current accepted status, including all associated references dealing with the historical nomenclatural changes and synonymy. We also provide up-to-date information on the diversity and distribution patterns of Charipinae to assist researchers working on these species in aphid biological control programs.